2008
DOI: 10.1590/s1517-86922008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de aminoácidos de cadeia ramificada não afeta o desempenho de endurance

Abstract: A relação entre o consumo de proteínas e o desempenho físico vem de longa data. Este tipo de associação pode ser encontrado até na mitologia grega. A lenda sobre Milo de Crotona, um grande lutador grego que viveu em meados de 500 a.C., confirma a preocupação com a dieta rica em proteínas já na antiguidade. Segundo a mitologia, tal lutador tinha sua força atribuída ao consumo elevado de carne, 8,5kg em um único dia.Em meados de 1840, Von Liebger foi um dos primeiros fisiologistas a abraçar a hipótese de que os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…For instance, a double-blind controlled randomized study showed that 21 g of BCAA supplementation over a week does not enhance vertical jump performance in professional volleyball players [ 11 ]. According to another study, BCAA supplementation after a treadmill test did not provide any differences in the sensation of fatigue and plasma concentration of glucose, lactate, or ammonia [ 12 ]. In contrast, Gualano et al (2011) demonstrated that BCAA supplementation increases exercise capacity and lipid oxidation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a double-blind controlled randomized study showed that 21 g of BCAA supplementation over a week does not enhance vertical jump performance in professional volleyball players [ 11 ]. According to another study, BCAA supplementation after a treadmill test did not provide any differences in the sensation of fatigue and plasma concentration of glucose, lactate, or ammonia [ 12 ]. In contrast, Gualano et al (2011) demonstrated that BCAA supplementation increases exercise capacity and lipid oxidation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Com o intuito de avaliar o efeito da ingestão do BCAA sobre o exercício de endurance realizado até a exaustão, Uchida et al [25] realizaram um estudo duplo cego e randomizado com 17 soldados brasileiros. Eles foram divididos em 2 grupos, os que consumiram 77 mg/kg de BCAA e os que consumiram 64 g de maltodextrina (placebo) durante os treinos.…”
Section: Tabela I -Valores De Percentual De Gordura (%) De Atletas Fu...unclassified
“…However, some research results show disagreement. In studies of Uchida et al [36] and Van Hall et al [37], the authors sought to analyze if the consumption of BCAA could somehow influence the performance of resistance exercise. They concluded that no significant differences were found in time of exhaustion analyzed, which means that the consumption of BCAA did not affect the performance in tests.…”
Section: Effects On Physical Performance In Endurance Exercisementioning
confidence: 99%